FDI in India and Other Asian Countries - Gupta, Sahil (2011)
The Sub-continent has become the prime target for foreign direct investment. The economic policies of India have been tailor made to specifically attract substantial inflow of capital into the Indian market and to sustain such inflows of capital. The Indian Government is constantly innovating to make the country an investor friendly destination and this attitude is reaping good results. The economic policies and economic reforms initiated by the Government had resulted in India being ranked the second position in attracting foreign direct investments (FDI). This ranking was conferred in 2010 by the United Nations Conference on Trade and Development (UNCTAD). The ranking was published in a report of UNCTAD titled: “World Investment Prospects Survey 2009-2012”. The said report has made the investment climate in India more favourable than ever before. The report also forecast that soon the country is going to feature among the top 5 investment destinations for investor from the world in the period 2010 to 2012. In May 2011 the inflow of FDI was more than hundred percent at US $ 4.66 billion. This amount has been the highest monthly investment in a single month for the last thirty nine months. Cumulatively, the total amount of FDI in India for the period April-May 2011 stands at around US$ 205.96 billion. This figure is according to the latest data released by the Department of Industrial Policy and Promotion (DIPP). Of all the sectors that drew FDI during the latest year, the highest FDI was drawn by the services sectors which included both the financial as well as non-financial sectors. The amount of FDI was US$ 910 million. Of the flow of FDI from countries, Mauritius topped the investment, investing close to US$ 56.31 billion while Singapore was the second largest foreign investor at US$ 13.25 billion. The US stood at the third place in investment, investing about US$ 9.71 billion. The period of the above said investment was between April 2000 to May 2011. The Forex reserves which are also known as foreign exchange reserves have increased significantly by US$ 2.29 billion. This amount is for the week that ended on 22nd July 2011. The above data was released by the Reserve Bank of India which is also known as RBI in it’s weekly statistical report. Similarly the foreign currency assets stood at US$ 284.53 billion from US$ 2.23 billion for the same period. It is also predicted that India might become the largest market of the US Export-Import Bank in the coming year and a half or so. This paper analysis the structure of economic reforms during the pre- independence and post independence era in the context of growth of foreign direct investment and the risks posed by the political, economic and social conditions for foreign investors. Essentially, this paper seeks to analyse and understand the politico-economic dynamics in relation to the country’s progressive integration with other major economies of the world which has put India on the global economic map.